Final Answer:
If ( t = -3 ), then
equals 0.
Step-by-step explanation:
To find the value of
when ( t = -3 ), substitute (-3) for ( t ) in the expression:
![\[ 3(-3)^2 + 5(-3) + 6 \]](https://img.qammunity.org/2020/formulas/mathematics/middle-school/omrjuo8wc65i4k4cpovpy0w1shrmxbsg3i.png)
= 3(9) - 15 + 6
= 27 - 15 + 6
= 12 - 15
= -3
Therefore, when ( t = -3 ), \
evaluates to (-3).
Understanding how to substitute values into algebraic expressions is fundamental in algebra. In this case, replacing ( t ) with (-3) allows us to find the specific value of the expression for that given input.
It's worth noting that this expression equals 0 for ( t = -3 ). This is an interesting mathematical result, indicating that the expression
making it equal to 0 when either \
This connection between factors and roots is a crucial concept in algebra.